Plagiarism In English Language Theses In Indonesia - Like Raskova Octaberlina (Universitas Negeri Malang, 2016)
This article argues that plagiarism in Indonesia exists due to some reasons. The reasons range from the requirements on the part of the students to adhere to uniformity in terms of thesis format to failure on the part of the government to effectively enforce a regulation dealing with plagiarism. Anecdotal observations as a student in one Indonesian university will give color to the discussion throughout this article. A recommendation to subdue plagiarism in Indonesia will conclude the article.